Independence and the Irish Environmental Protection Agency: A Comparative Assessment - Shipan, Charles (Trinity College Dublin, 2006)
The Environmental Protection Agency is one of the most prominent regulatory agencies in Ireland. Created in 1992, one of the hallmarks of this agency is its independence from other parts of government. Yet little is known about the actual extent of its independence. Independence and the Irish Environmental Protection Agency: A Comparative Assessment addresses several key questions about the agency's independence. Why was independence such a primary justification for the creation of this agency? How does the agency's level of independence compare with that of other independent regulatory agencies in Ireland? How does its level of independence compare with environmental regulatory agencies elsewhere in Europe and the US? Do the actions of the agency indicate sensitivity to signals that the government sends? This study uses historical evidence, interviews, and statistical comparisons in order to address these questions. The topics covered by these questions are important not only on their own, for what they can tell us about the agency's level of independence, but also because of the relationship between independence and accountability. Furthermore, Ireland is currently reassessing its overall regulatory programme, and any potential reforms must be informed by a firm understanding of an agency's structural characteristics and independence, the sort of understanding that this study provides.
Keywords: Social Policy; Environmental Protection Agency; Ireland